Pembuatan Kopi Celup Dengan Varian Rasa Rempah Sebagai Imunitas - Fitriana Bunyanis; Wahyuni L Ode; Dewi Lidiawati; Rustam T (JPM: Jurnal Pengabdian Masyarakat, 2023)
The development of the domestic coffee processing industry has very good prospects, considering that the Indonesian people's consumption of coffee is very high. Dip coffee is a modification of making coffee by adding some herbal plants that have been processed or dried and mashed and then put into a ceh canton. The purpose of making Dip Coffee as Immunity. The ingredients used in the manufacture of Dip Coffee, namely Cloves, are used as mouth freshener, to treat boils and toothaches, as pain relievers, food flavoring and fragrances. The part used is Flowers. Ginger Strengthens the Immune System Prevents Bacterial and Viral Infection Relieves Muscle Pain Relieves Morning Sickness Parts used Ginger Rhizome, Lemongrass Increases immunity, Reduces cholesterol in the blood, Improves sleep quality, and relieves pain, Cinnamon Medicine for colds, diarrhea, stomach bloating, no appetite, headaches, canker sores, asthma, gout medications, high blood pressure and other problems related to the digestive tract. Coffee for Central Nervous Stimulation. In this activity, the community does not only get counseling about dip coffee, but the community can find out about the manufacture of dip coffee and what ingredients are in the contents of the dip coffee.